Prevalence of Arboviruses in Vietnam - Zh. A. Kas’yan; E. V. Naidenova; M. V. Proskuryakova; E. A. Mikheeva; T. V. Toan; B. T.T. Nga; V. V. Cuong; V. V. Kutyrev (Проблемы особо опасных инфекций, 2022)
For many years, arbovirus infections have been a global health problem and one of the urgent threats to the sanitary and epidemiological well-being of the population. Climatic conditions, species diversity and abundance of vectors, epidemiological and demographic factors are of fundamental importance for the emergence and persistence of natural foci of arbovirus infections. In the Socialist Republic of Vietnam (SRV) and other countries of the Asia-Pacific region, the most complex epidemiological situation is observed in regard to a number of arboviral infectious diseases transmitted by mosquitoes, inter alia to dengue fever. In this review we analyzed the literature data to identify the features of the circulation of some arboviruses in Vietnam, such as dengue virus, Zika, Chikungunya, Japanese encephalitis virus, Dabie virus, and the routes of their transmission and spread. It is shown that the climatic, ecological, epidemiological and demographic conditions existing on the territory of Vietnam contribute to the spread of pathogens of many arboviruses. Areas of more active circulation and ways of spreading pathogens of arbovirus infections have been identified. Based on the data obtained, it is necessary to conduct annual epidemiological and epizootiological survey of the territory of the SRV in order to identify markers of pathogens and determine the boundaries of natural foci of arbovirus infectious diseases which will enhance and increase the effectiveness of preventive and anti-epidemic measures.